2016
DOI: 10.1128/genomea.00002-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Porcine Epidemic Diarrhea Virus Strain from Vietnam, HUA-14PED96, with a Large Genomic Deletion

Abstract: A highly virulent strain of Porcine epidemic diarrhea virus (PEDV) causing severe diarrhea has recently emerged in Vietnam. Genomic sequences from a novel strain, HUA-14PED96, isolated from a Vietnamese piglet with serious diarrhea show relatively high identity with U.S.-like PEDV strains, and have a 72-nt deletion in the open reading frame 1a (ORF1a) gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Two recent studies reported that five Vietnamese PEDV strains isolated in 2013 and early 2014 including VN/JFP1013_1/2013/Vinh An/Vietnam, VN/VAP1113_1/2013/Vung Tua/Vietnam, VN/KCHY‐310113/2013/KhoaiChau/HungYen/Vietnam (Vui et al., ), HUA‐PED45 and HUA‐PED47 2010 (Kim, Lim et al., ) were related to new Chinese variants that have emerged since 2010. The Vietnamese PEDV strain HUA‐14PED96 (accession number KT941120), which was identified in a Northern province, was reported to have a unique 72‐nucleotide deletion in the ORF1a gene (Choe et al., ). Consistent with the previous results, several Vietnamese PEDV strains in our study were genetically similar to the reported Vietnamese strains and re‐emerging Chinese strains.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that five Vietnamese PEDV strains isolated in 2013 and early 2014 including VN/JFP1013_1/2013/Vinh An/Vietnam, VN/VAP1113_1/2013/Vung Tua/Vietnam, VN/KCHY‐310113/2013/KhoaiChau/HungYen/Vietnam (Vui et al., ), HUA‐PED45 and HUA‐PED47 2010 (Kim, Lim et al., ) were related to new Chinese variants that have emerged since 2010. The Vietnamese PEDV strain HUA‐14PED96 (accession number KT941120), which was identified in a Northern province, was reported to have a unique 72‐nucleotide deletion in the ORF1a gene (Choe et al., ). Consistent with the previous results, several Vietnamese PEDV strains in our study were genetically similar to the reported Vietnamese strains and re‐emerging Chinese strains.…”
Section: Discussionmentioning
confidence: 99%
“…It contains a 72 nt-deletion in the open reading frame 1a (ORF1a), corresponding to a 24 aa-DEL in the nsp3 protein, and is grouped with the Chinese highly virulent PEDV cluster ( Fig. 1) (Choe et al, 2016).…”
Section: Pedv Variants That Have Deletions In the Orf1a Regionmentioning
confidence: 99%
“…In Vietnam, PEDV was first observed in the southern provinces in 2009 (21). Published studies have demonstrated that PEDV is present in all major swine-producing regions in Vietnam (21)(22)(23)(24)(25)(26). A descriptive survey recently provided evidence that northern Vietnam is an endemic area for PEDV, with a high proportion of PED-positive farms (30.89%) (Mai et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%